Повышение эффективности работы персонала фирмы - Сильченко, А.В. (Культура народов Причерноморья, 2014)
Рассмотрены основные теоретические аспекты персонала в менеджменте и роль на
предприятии туриндустрии. Определена необходимость повышения эффективности деятельности
персонала на предприятии туриндустрии. Рассмотрено применение мотивации на фирме, её позитивное
влияние на повышение эффективности и конкурентоспособности предприятия. Рекомендации, проведенные в
исследовании, могут обеспечить и эффективность фирмы туристической индустрии и удовлетворить
потребности персонала. Розглянуті основні теоретичні аспекти персоналу в менеджменті і роль на підприємстві
туріндустрії. Визначена необхідність підвищення ефективності діяльності персоналу на підприємстві
туріндустрії. Розглянуто вживання мотивації на фірмі, її позитивний вплив на підвищення ефективності і
конкурентоспроможності підприємства. Дані рекомендації можуть забезпечити і ефективність фірми
туристичної індустрії і задовольнити потреби персоналу. The basic theoretical aspects of leadthrough of marketing and role are considered on the enterprise of
turindustrii. The necessity of application of marketings strategies is certain on the enterprise of turindustrii.
Consideration of introduction of innovations is in marketing, their positive influence on an increase arrived increase of
competitiveness. These recommendations can provide and efficiency of enterprise of tourist industry and to satisfy the
necessities of users. Actuality of theme consists of that every organization aspires to the increase of the labour
productivity. It is for this purpose necessary to be engaged in the increase of efficiency of activity of personnel. In
modern market conditions the administrative vehicle of any enterprise for the effective selection of shots must take into
account not only professional qualities of workers but also level of their stability. Labour is related straight to intensity
of development of production, and also with the use of CASS, information, computer technologies. Word «Personnel»
the Latin origin and a person means. In a management a personnel is interpreted as an aggregate of people which
create organization and consist with it of labour relations on the basis of individual agreements, by getting busy social
and political activity. Organization is an association of people, directed on achievement of general purpose. Exactly
orientation on achievement of general purpose able to promote efficiency of activity.